Alternatives of perfluoroalkyl acids and hepatitis B virus surface antibody in adults: Isomers of C8 Health Project in China. (April 2020) - Zeng, Xiao-Wen; Li, Qing-Qing; Chu, Chu; Ye, Wan-Lin; Yu, Shu; Ma, Huimin; Zeng, Xiao-Yun; Zhou, Yang; Yu, Hong-Yao; Hu, Li-Wen; Yang, Bo-Yi; Dong, Guang-Hui
Abstract: Previous epidemiological and experimental studies have shown that legacy perfluoroalkyl acids (PFAAs) are immunotoxic. However, whether the immunosuppressive effects in PFAA alternatives which recently have been widely detected in the environment are unknown. To address this knowledge gap, we investigated the relationship of serum legacy PFAAs and PFAA alternatives with the antibody of hepatitis B virus in adults. We recruited 605 participants from a cross-sectional study, the Isomer of C8 Health Project in China. We measured two representative legacy PFAAs (perfluorooctane sulfonate, PFOS and perfluorooctanoic acid, PFOA), and three PFAA alternatives (two chlorinated polyfluorinated ether sulfonic acids, Cl-PFESAs and perfluorobutanoic acid, PFBA) in serum using ultra-performance liquid chromatograph-tandem mass spectrometry (UPLC-MS/MS). We applied linear and logistic regression models to analyze associations between serum PFAAs and hepatitis B surface antibody (HBsAb) with multivariable adjustments. We found negative associations between serum PFAAs concentrations and HBsAb. Lower serum HBsAb levels (log mIU/mL) were observed for each log-unit increase in linear PFOS (β = −0.31, 95% confidential interval: 0.84, −0.18), 6:2 PFESA (β = −0.81, 95% CI: 1.20, −0.42), 8:2 PFESA (β = −0.29, 95% CI: 0.43, −0.14) and PFBA (β = −0.18, 95% CI: 0.28, −0.08). The association between PFAAs and HBsAb seronegative seemed to be higher for 6:2 PFESA (odds ratio = 3.32, 95% CI: 2.16, 5.10) than its predecessors, linear PFOS (OR = 1.96, 95% CI: 1.37, 2.81) and branched PFOS isomers (OR = 1.64, 95% CI: 1.05, 2.56). We report new evidence that exposure to PFAA alternatives are associated with lower HBsAb in adults. This association seems to be stronger in 6:2 PFESA than PFOS. Our results suggest that more studies are needed to clarify the potential toxicity of PFAA alternatives in human which will facilitate better chemical regulations for PFAAs. Graphical abstract: Image 1 Highlights: Legacy perfluoroalkyl acids and PFAA alternatives were widely detected in serum. Higher serum PFAAs were associated with lower hepatitis B virus antibody levels. The observed association was stronger for a chlorinated PFAA alternative.